PENGARUH MODEL COOPERATIF LEARNING TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA PADA MATERI WUJUD ZAT DAN PERUBAHANNYA DI KELAS IV UPTD SD INPRES PERUMNAS 2 KOTA KUPANG - Ana Maria L. Pereira; Angelikus N. Koten, Adam B. N. Benu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes of students on the material of the state of matter and its changes in class IV UPTD SD Inpres Perumnas 2 Kupang City. The purpose of this study was to determine the effect of the JIGSAW type cooperative learning model on student learning outcomes on the material of the state of matter and its changes in class IV UPTD SD Inpres Perumnas 2 Kupang City. The method used is quantitative with 'one group pretests-posttest design, with a research sample of 30 students using total sampling technique (saturated sample). Data were collected through observation and tests and analyzed using the t-test. The results of the study showed that there was an effect of the cooperative learning model on student learning outcomes on the material of the state of matter and its changes in class IV UPTD SD Inpres Perumnas 2 Kupang City. This is evidenced by the data from the research conducted by the researcher which showed a comparison of the average posttest of 83.57> from the average pretest value of 54.50. Furthermore, the results of the hypothesis testing that has been formulated can be seen that the sig value (2-tailed) is 0.000 <0.05, so it can be concluded that H0 is rejected and H1 is accepted, which means that the hypothesis in this study is accepted, namely that there is a positive influence of the implementation of the JIGSAW type Cooperative Learning model on student learning outcomes on the material of the form of matter and its changes in class IV UPTD SD Inpres Perumnas 2 Kupang City.